Fecal Fungal Dysbiosis in Chinese Patients With Alzheimer’s Disease - Ling, Zongxin; Zhu, Manlian; Liu, Xia; Shao, Li; Cheng, Yiwen; Yan, Xiumei; Jiang, Ruilai; Wu, Shaochang (Frontiers in Cell and Developmental Biology, 2021)
Gut bacterial dysbiosis plays a vital role in the development of Alzheimer’s disease (AD). However, our understanding of alterations to the gut fungal microbiota and their correlations with host immunity in AD is still limited. Samples were obtained from 88 Chinese patients with AD, and 65 age- and gender-matched, cognitively normal controls. Using these samples, we investigated the fungal microbiota targeting internal transcribed spacer 2 (ITS2) rRNA genes using MiSeq sequencing, and analyzed their associations with the host immune response. Our data demonstrated unaltered fungal diversity but altered taxonomic composition of the fecal fungal microbiota in the AD patients. The analysis of the fungal microbiota was performed using 6,585,557 high-quality reads (2,932,482 reads from the controls and 3,653,075 from the AD patients), with an average of 43,042 reads per sample. We found that several key differential fungi such as Candida tropicalis and Schizophyllum commune were enriched in the AD patients, while Rhodotorula mucilaginosa decreased significantly. Interestingly, C. tropicalis and S. commune were positively correlated with IP-10 and TNF-α levels. In contrast, C. tropicalis was negatively correlated with IL-8 and IFN-γ levels, and R. mucilaginosa was negatively correlated with TNF-α level. PiCRUSt analysis revealed that lipoic acid metabolism, starch and sucrose metabolism were significantly decreased in the AD fungal microbiota. This study is the first to demonstrate fecal fungal dysbiosis in stable AD patients at a deeper level, and to identify the key differential fungi involved in regulating host systemic immunity. The analysis of the fungal microbiota in AD performed here may provide novel insights into the etiopathogenesis of AD and pave the way for improved diagnosis and treatment of AD.